2014
DOI: 10.1615/intjmedmushr.v16.i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Potential of Polysaccharides from the White Oyster Culinary-Medicinal Mushroom Pleurotus florida (Higher Basidiomycetes)

Abstract: This study was designed to examine the antihyperglycemic potential of the polysaccharide fraction of Pleurotus florida. Hyperglycemia was induced by streptozotocin (50 mg/kg intraperitoneal). Single- and multiple-dose studies were performed to assess the antihyperglycemic potential of the P. florida polysaccharides (PFPs). Organisation for Economic Co-operation and Development guideline 423 was followed to study the acute toxicity of PFP. PFP was found to be nontoxic up to 4000 mg/kg. In this investigation, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…P. florida decreased the levels of MDA and nitric oxide and restored the levels of GSH, SOD, and CAT in diabetic rats. These findings recommended that administration of P. florida could attenuate diabetic complications along with hyperglycemia and hypercholesteremic effects [102]. Based on the investigations, all these results strongly suggest that polysaccharides possess antioxidant properties that can be applied as an adjunct therapy and control the effect of T2DM.…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 93%
“…P. florida decreased the levels of MDA and nitric oxide and restored the levels of GSH, SOD, and CAT in diabetic rats. These findings recommended that administration of P. florida could attenuate diabetic complications along with hyperglycemia and hypercholesteremic effects [102]. Based on the investigations, all these results strongly suggest that polysaccharides possess antioxidant properties that can be applied as an adjunct therapy and control the effect of T2DM.…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 93%
“…Treatment with Pleurotus florida polysaccharides significantly reduced glucose, serum cholesterol, triglycerides, and ketones in animals. The study concluded that polysaccharides could improve hyperglycemia and hypercholesterolemia, including other complications in the therapy of type 2 diabetes mellitus [ 131 , 132 ]. A comparative study on six edible and medicinal mushrooms was reported for their antidiabetic potential in terms of the inhibitory action of the α-amylase and α-glucosidase.…”
Section: Pharmacological and Pharmaceutical Propertiesmentioning
confidence: 99%
“…Mushroom polysaccharides are reported to lessen the symptoms of medical conditions associated with metabolic syndrome, including diabetes [ 153 ]. Polysaccharides that have been reported to have antidiabetic properties in diabetic and/or obese rodents include those from the following mushroom varieties: Agaricus brasiliensis [ 154 ]; Agrocybe chaxingu [ 155 ]; Catathelasma ventricosum [ 18 ]; Grifola frondosa [ 156 ]; Phellinus linteus; [ 56 ]; Pleurotus abalonus [ 157 ]; Pleurotus eryngii [ 158 ]; Pleurotus florida [ 159 ]; Pleurotus sajor-caju [ 160 ]; Tremella fuciformis [ 151 ]; Ganoderma lucidum [ 161 ]; Lentinus strigosus [ 162 ]; Pleurotus tuber-regium [ 123 ]; Sparassis crispa [ 163 ]; and Tremella aurantialba [ 164 , 165 , 166 ]. Several of these studies will be elaborated on further below.…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%
“…A polysaccharide isolated from the culinary–medicinal Pleurotus florida mushrooms was found to be nontoxic to mice up to 4000 mg/kg body weight [ 159 ]. The treatment of diabetic mice with the polysaccharide (200 and 400 mg/kg) resulted in significant reduction of the plasma glucose, serum cholesterol, triglycerides, malondialdehyde, nitric oxide, and urine glucose and ketones concentrations.…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%